Usługi sieciowe jako element działań integracyjnych - Fliegner, Wojciech (Web Services in the Integration Activities, 2005)
Web services technologies are beginning to emerge as a de facto standard for integrating disparate applications and systems using open, XML-based standards. In addition to building web services interfaces to existing applications, there must also be a standard approach to connecting these web services together to form more meaningful business processes. In this paper, we briefly introduce the problem of integration and, based on an architectural perspective, give an overview of approaches to address the integration issue. This article discusses also the usefulness of Web Services in EAI and B2B.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1081, s. 358-366